An analytical longitudinal observational study on the association of Vitamin D insufficiency in subjects with primary (idiopathic) demyelinating optic neuritis using visual evoked potential and optical coherence tomography - Nirja Agasti,; Amar Kumar Misra,; Mandal, Manamita; Bijendra Mohanty,; Soumit Roy,; Joydeep Mukherjee,; Jasodhara Chaudhuri, (Asian Journal of Medical Sciences, 2024)
Background: Optic neuritis (ON) is an acute and often immune-mediated inflammatory condition of the optic nerve. Vitamin D acts as an anti-inflammatory agent and may confer neuroprotection. Visual evoked potential (VEP) and optical coherence tomography (OCT) are emerging tools for demyelinating diseases. Aims and Objectives: We tried to correlate between Vitamin D insufficiency and acute demyelinating ON using different parameters such as VEP, ganglion cell layer (GCL) thickness, and retinal nerve fiber layer (RNFL) thickness. Materials and Methods: This observational longitudinal analytical study included thirty non-consecutive patients with primary ON and 30 healthy controls. All patients with ON underwent detailed clinical and ophthalmological examination, and detailed blood workup, including serum 25 (OH) Vitamin D. VEP P100 latency, amplitude, OCT, RNFL thickness, and GCL thickness at presentation and after 3 months from May 2019 to November 2020. Results: Vitamin D insufficiency (below 30 ng/mL) was present in 60% of cases of ON. The baseline VEP showed significantly prolonged P100 latency in affected eyes in the Vitamin D insufficient group (mean 129.78±7.97 ms vs. 121.0±4.99 ms) whereas the P100 amplitude was not significantly altered between the two groups (5.5±3.13 μV vs. 7.08±3.01 μV). The baseline RNFL thickness (132.21±10.69 μm vs. 118.01±10.4 μm) and GCL thickness (76.82±2.04 μm vs. 73.06±3.2 μm) were greater in affected eyes of vitamin D insufficiency ON. There was greater RNFL thinning (79.93±3.42 μm vs. 74.80±3.5 μm) and GCL thinning (64.78±1.9μm vs. 69.02±2.22 μm) in affected eyes of ON with Vitamin D insufficiency at 3 months. Conclusion: Vitamin D insufficiency was found in most cases of ON. Insufficient Vitamin D positively correlated with optic nerve affection severity as evidenced by significantly increased baseline thickness of RNFL and GCL and more thinning of RNFL and GCL at the end of 3 months of follow-up.